Application of Direct Learning Model to Improve Learning Outcomes of Islamic Religious Education in SD Negeri 11 Sampoiniet - Irawati , Nelly (Jurnal Profesi Guru Indonesia, 2024)
Learning is an important process that determines the success of education. Improving the quality of education, especially in schools, cannot be separated from the success of the teaching and learning process. The teaching and learning process is influenced by several components, among them: teachers, students, teaching methods, learning media, student activity and student motivation in learning. These components play an important role in determining the success of the learning process so that they will influence the learning outcomes. The purpose of this research is to find out the application of the direct learning model in class III Islamic religious education, to improve student learning outcomes. The subjects of the research are 30 students of Class III SD Negeri 11 Sampoiniet, Aceh Jaya Regency, Aceh Province, consisting of 16 girls and 14 boys. This research uses the class action research model (PTK), with 2 cycles and each cycle consists of planning, action, observation and reflection. There are 2 research instruments in this research, namely: a test instrument and a non-test instrument (observation). Data analysis techniques are based on cycle results from each learning process. The learning outcomes of mathematics students in the direct instruction model show an improvement. Based on the results of the research, the teacher's activity in cycle 1 was in the good category, while in cycle 2 the teacher's activity was in the very good category. This means there is a change in teachers' activities for the better. While the result of obtaining the average value in cycle 1 was 60.2 with a completion rate of 50%, then in cycle 2 the average value was 71.25 with a completion rate of 83.3%. The average value from cycle 1 and cycle 2 shows an increase.